Pemberdayan dan Peningkatan Minat Belajar di Desa Remitie yang Berkelanjutan Kec. Sungai Mas Kab. Aceh Barat - Suhelmi; Verial Wariski; Mutiara Saitun; Lidia Nurkhaliza; Kasfa Sella Maulida; Thary Silvya; Selly Suci Rahayu; Milda Chandra Ilona; Saiful Amri (Jurnal Ragam Pengabdian, 2025)
Education is a key foundation for improving the quality of life in rural communities. In Ramitie Village, Sungai Mas Subdistrict, West Aceh, children and adolescents still show low interest in learning, mainly due to limited facilities and the lack of consistent guidance. The 2025 Community Service Program (KKN) of Teuku Umar University was designed to address this challenge through regular tutoring sessions, creative skills training, the establishment of a reading corner, and awareness campaigns on the importance of education. The program applied a participatory approach, engaging local residents, village officials, and community leaders throughout its planning and implementation. The results indicate increased learning motivation, improvement in basic literacy and numeracy skills among children, and stronger collective awareness of education’s role in community development. Furthermore, a village study group was established to ensure program sustainability after the KKN period. These findings highlight that empowerment based on collaboration can foster a culture of learning while strengthening human resource development in rural areas.